Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Colorectal Cancer in the American Indian and Alaska Native Community: A Holistic Review - Angela R. Monetathchi; William O. Carson; Byron Upshaw; Autumn Lester; Emma Cleary; Alyssa Little; Felina M. Cordova-Marks; Jennifer Erdrich (Journal of Cancer Education, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Associations of volatile organic compounds with accelerated epigenetic aging in the lungs of smokers and electronic cigarette users - Ajmal Khan; Carson Richardson; Joseph P. McElroy; Amarnath Singh; Daniel Y. Weng; Sahar Kamel; Sarah A. Reisinger; Mark D. Wewers; Peter G. Shields; Min-Ae Song (Science of The Total Environment, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Understanding and valuing human connections to deep-sea methane seeps off Costa Rica - Olívia S. Pereira; Mark Jacobsen; Richard Carson; Jorge Cortés; Lisa A. Levin (Ecological Economics, 2024)

Invasive shrubs differentially alter autumnal activity for three common small‐mammal species - Brian Connolly; Chad R. Zirbel; Carson Keller; Mark Fuka; John L. Orrock (Ecology, 2024)
Seasonal variation in animal activity influences fitness and the intensity of ecological interactions (e.g., competition, predation), yet aspects of global change in the Anthropocene may catalyze shifts in seasonal activity. Invasive plants are components of global change and can modify animal daily activity, but their influence on animal seasonal activity is less understood. We examined how invasive woody shrubs (Autumn olive [ Elaeagnus umbellata ] and Amur honeysuckle [ Lonicera maackii ]) affect seasonal activity of three common small‐mammal species by coupling experimental shrub removal with autumnal camera trapping for two consecutive years at six paired forest sites (total 12 plots). Eastern chipmunks ( Tamias striatus ) foraged more, and foraging was observed at least 20 days longer, in shrub‐invaded forests. White‐footed mice ( Peromyscus leucopus ) foraged more in invaded than cleared plots in one study year, but P. leucopus autumn activity timing did not differ between shrub‐removal treatments. Fox squirrel ( Sciurus niger ) activity displayed year‐specific responses to shrub removal suggesting intraannual cues (e.g., temperature) structure S. niger autumnal activity. Our work highlights how plant invasions can have species‐specific effects on seasonal animal activity, may modify the timing of physiological processes (e.g., torpor), and could generate variation in animal‐mediated interactions such as seed dispersal or granivory.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

RNA sequencing of LX-2 cells treated with TGF-β1 identifies genes associated with hepatic stellate cell activation - Jack P. Carson; Mark W. Robinson; Grant A. Ramm; Geoffrey N. Gobert (Molecular Biology Reports, 2021)
Background Hepatic stellate cells (HSCs) are liver-resident myofibroblast precursors responsible for the production of collagen and maintenance of the hepatic extracellular matrix (ECM). As such, they are generally associated with fibrotic liver diseases. HSCs become “activated” in response to tissue damage or pathogen invasion, a process most commonly driven by transforming growth factor-β1 (TGF-β1). Despite this, the full extent of TGF-β1 signalling in these cells is poorly understood. Clarifying the range and diversity of this signalling will further improve our understanding of the process of HSC activation. Methods and results RNA sequencing was used to quantitate the transcriptomic changes induced in LX-2 cells, an activated human HSC line, following TGF-b1 treatment. In total, 5,258 genes were found to be significantly differentially expressed with a false discovery rate cut-off of < 0.1. The topmost deregulated of these genes included those with no currently characterised role in either HSC activation or fibrotic processes, including CIITA and SERPINB2. In silico analysis revealed the prominent signalling pathways downstream of TGF-β1 in LX-2 cells. Conclusions In this study, we describe the genes and signalling pathways significantly deregulated in LX-2 cells following TGF-β1 treatment. We identified several highly deregulated genes with no currently characterised role in HSC activation, which may represent novel mediators of fibrotic responses in HSCs or the liver macroenvironment. This work may be of use in the identification of new markers of liver fibrosis and could provide insight into prospective genes or pathways that might be targeted for the amelioration of fibrotic liver disease in the future.

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

How SARS-CoV-2 might affect potassium balance via impairing epithelial sodium channels? - Maryam Noori; Seyed Aria Nejadghaderi; Mark J. M. Sullman; Kristin Carson-Chahhoud; Mohammadreza Ardalan; Ali-Asghar Kolahi; Saeid Safiri (Molecular Biology Reports, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Climate Model Uncertainty and Trend Detection in Regional Sea Level Projections: A Review - Mark Carson; Kewei Lyu; Kristin Richter; Mélanie Becker; Catia M. Domingues; Weiqing Han; Laure Zanna (Surveys in Geophysics, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Reduced white matter MRI transverse relaxation rate in cognitively normal H63D-HFE human carriers and H67D-HFE mice - Mark D. Meadowcroft; Jianli Wang; Carson J. Purnell; Douglas G. Peters; Paul J. Eslinger; Elizabeth B. Neely; David J. Gill; Megha Vasavada; Fatima Ali-Rahmani; Qing X. Yang; James R. Connor (Brain Imaging and Behavior, 2016)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Recent sea level and upper ocean temperature variability and trends; cook islands regional results and perspective - D. E. Harrison; Mark Carson (Climatic Change, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Real-time error detection but not error correction drives automatic visuomotor adaptation - Mark R. Hinder; Stephan Riek; James R. Tresilian; Aymar de Rugy; Richard G. Carson (Experimental Brain Research, 2010)

Microsatellite markers for species of the genus Dionda (Cyprinidae) from the American southwest - Mark A. Renshaw; Evan W. Carson; Ashley H. Hanna; Caird E. Rexroad; Trevor J. Krabbenhoft; John R. Gold (Conservation Genetics, 2009)

Muscle wasting and interleukin-6-induced atrogin-I expression in the cachectic Apc Min/+ mouse - Kristen A. Baltgalvis; Franklin G. Berger; Maria Marjorette O. Peña; J. Mark Davis; James P. White; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2009)

The efficacy of colour cues in facilitating adaptation to opposing visuomotor rotations - Mark R. Hinder; Daniel G. Woolley; James R. Tresilian; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2008)

The interference effects of non-rotated versus counter-rotated trials in visuomotor adaptation - Mark R. Hinder; Laura Walk; Daniel G. Woolley; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2007)

The effect of obstacle position on reach-to-grasp movements - Vanessa L. Coppard; James R. Tresilian; Mark Mon-Williams; Richard G. Carson (Experimental Brain Research, 2001)